Effects of colours, shapes and icons on performance and familiarity - Dambuza, Inga Yola (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2011)
Occupational injuries and illnesses remain to be a heavy burden on workers and employees in industrial developing and industrially developed societies, and health and safety in workplaces continues to be an important issue for ergonomists. Steps are being taken to stimulate health and safety agendas and to discover ways in which health and safety in industries can be improved. The main responsibility of employers is to provide employees with information, instructions and training that they required to carry out their work tasks in a healthy, practical and safe manner. The role of education as a countermeasure to occupational injury and illness is being re-examined by health and safety practitioners and safety training is being considered as a vital part of accident prevention strategies. Effective training programmes should guarantee that workers possess the skills they require to complete their tasks in a safe and healthy manner. Very little is known about the type and quality of training workers undergo and how that training affects the safety outcomes of companies. There has been an attempt over the past 20 years to increase the research on safety communications and a great deal of this research has been focused on safety warnings; with the greatest attention been placed on the components of safety signs, such as colours, size, shapes and icons. The effects of these components on comprehension with relation to age and education have not received the same amount of attention. The impact of familiarity on safety warnings with respect to age and education has also received very little attention; despite the knowledge that familiarity has been shown to increase the noticing of warnings and the comprehension of safety information. Despite the increase in the research on safety communication, the literature and research in South Africa is scarce. Studies present in South Africa do not encompass the comprehension of safety signs or the ability of individuals with different age and education levels to learn the information included in the signs. Due to the multi-linguistic nature of South Africa and the fact that South Africa is an Industrially Developing Country (IDC) with high levels of illiteracy, issues such as the comprehension of safety information must be addressed. Therefore, the objectives of this study were to investigate the effects of safety sign attributes on learning and familiarity, in subjects that differed in age and education levels. These effects were investigated through measuring the reaction and response times of the different subject groups, as well as the number of components in the safety signs that were recalled correctly. The combined results of these responses were used as a measure for familiarity. A set of signs was designed for the study by the researcher using three different colours, three different shapes, three different icons and text. Certain variables were omitted from some signs to create the test pool and the eight conditions that were tested in a laboratory setting. Each condition contained different components of the designed signs and 60 subjects were used to test these conditions. The subjects were placed in groups according to their age and level of education. Subjects were required to learn a set of 64 signs, either "With Occlusion" or "Without Occlusion" , and asked to recall the meanings of the components in the signs. Reaction time, response time and error rate were measured from the responses. The results showed that the conditions resulted in different reaction times, response times and error rates for all subjects. The signs containing a combination of shapes and text resulted in the best performance. Age and education were found to have a significant effect on various performance criteria as did the method in which the signs were displayed (Occlusion and No Occlusion). The increased repetitions and sessions elicited lower reaction times, response times and error rates. The conclusions drawn from this study suggest that different attributes be considered carefully when subjects are expected to learn and recall information in safety signs. The results also highlighted the need to increase the exposure of individuals to safety signs in order to increase familiarity and ultimately improve the recall and comprehension of the attributes.
Keywords: Industrial hygiene -- Research -- South Africa; Industrial safety -- Research -- South Africa; Industrial hygiene -- Standards -- South Africa; Human engineering -- Research -- South Africa